Navigator-based slice tracking for prospective motion correction in kidney vessel architecture imaging - Zhang, Ke; Triphan, Simon M. F.; Kurz, Felix T.; Ziener, Christian H.; Kauczor, Hans-Ulrich; Schlemmer, Heinz-Peter; Sedlaczek, Oliver (Magnetic resonance imaging, 2023)
Objectives - To apply a navigator-based slice tracking method to prospectively compensate the respiratory motion for kidney vessel architecture imaging (VAI). - Materials and methods - A dual gradient echo spin echo 2D EPI sequence was developed for kidney VAI. A single gradient-echo slice selection and projection readout at the location of the diaphragm along the inferior-superior direction was applied as a navigator. Navigator acquisition and fat suppression were inserted before each transverse imaging slice. Motion information was calculated after exclusion of the signal saturation in the navigator signal caused by imaging slices. The motion information was then directly sent back to the sequence and slice positioning was adjusted in real-time. The whole sequence was applied during a contrast agent pass-through. - Results - VAI parametric maps show the structural heterogeneity of the renal vasculature. The respiratory motion from the navigator signal was precisely calculated and slice positioning was changed in real-time based on the motion information. The vibration amplitude of the signal intensity of the liver tissue at the liver-lung interface in the case of prospective motion correction (PMC) on is about 28% of the PMC off case. Compared to the case of PMC off, the coefficient of variation was reduced 30% of the case of PMC on. - Conclusions - This study demonstrates the feasibility of the motion-compensating technique in kidney VAI. The sequence may improve the evaluation of microvasculature in kidney diseases.
Online verfügbar 2 January 2023, Version des Artikels 14 January 2023
Gesehen am 10.07.2023